Efeito do treinamento aeróbio nos níveis plasmáticos do fator neurotrófico derivado do cérebro, variáveis metabólicas e funções cognitivas em idosos com a doença de Alzheimer - Coelho, Flávia Gomes de Melo [UNESP] (2014)
The Alzheimer's disease (AD) patients have low expression of brain-derived neurotrophic factor (BDNF) in brain tissue. This reduction may be associated with increased cholesterol and insulin resistance, contributing to the progression of cognitive decline. Recent studies suggest that the physical exercise is effective for increasing BDNF concentrations in healthy older adults. However, there are no studies analyzing the effect of exercise on levels BDNF in AD. The study was divided into two parts. Study 1 aimed to evaluate the BDNF plasma levels, metabolic variables and cognitive functions of healthy older adults and AD patients (part 1) and to compare the effect of a session of aerobic exercise on BDNF levels in these two groups (part 2). Participated in the study 1, part 1, 75 older adults, 40 healthy older adults and 35 mild AD patients. The older adults were subjected to the following assessment tools: Mini Mental State Examination, Frontal Assessment Battery, Clock Drawing Test, Verbal Fluency Test, Test Search Symbols, Geriatric Depression Scale and blood collection to obtain BDNF plasma levels, metabolic variables (cholesterol, triglycerides, insulin and glucose). The One-Way ANOVA showed that AD patients had lower BDNF plasma levels compared to healthy older adults and the Mann Whitney U-test showed that AD patients had lower levels of HDL. Significant correlations between BDNF levels and HDL and between BDNF levels and Mini-Mental State Examination were found. In part 2, participated 21 AD patients and 18 healthy older adults. In this study were made all assessment tools of part 1 with inclusion of the incremental test, analysis of lactate levels, VO2, treadmill grade and treadmill time. The two-way ANOVA showed that acute aerobic exercise increased BDNF levels in AD patients and healthy older adults and significant correlation was found between the level of physical activity and BDNF concentrations. Study 2 aimed to analyze the...